2007
DOI: 10.1111/j.1743-6109.2007.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

The Female Prostate Revisited: Perineal Ultrasound and Biochemical Studies of Female Ejaculate

Abstract: Introduction Many speculations have been made on the possible existence of a “female prostate gland” and “female ejaculation.” Despite several reports on the subject, controversy still exists around the “female prostate” and whether such a gland might be the source of fluid emitted during orgasm (ejaculation). Aim To investigate the ultrasonographic, biochemical, and endoscopic features in two women who reported actual ejacul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
1
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 30 publications
1
52
1
7
Order By: Relevance
“…Male prostates produce a glycoprotein secretion that is essential to maintain an adequate environment for spermatozoid survival and is thus critical for reproductive success in mammals that present internal fertilization. Recent studies have shown that women's prostatic secretion has a biochemical composition very similar to the one found in prostatic plasma of men (Wimpissinger et al, 2007).…”
mentioning
confidence: 99%
“…Male prostates produce a glycoprotein secretion that is essential to maintain an adequate environment for spermatozoid survival and is thus critical for reproductive success in mammals that present internal fertilization. Recent studies have shown that women's prostatic secretion has a biochemical composition very similar to the one found in prostatic plasma of men (Wimpissinger et al, 2007).…”
mentioning
confidence: 99%
“…Although PSA is mainly present in the prostate tissue and semen, it has also been detected in malignant breast tumors [5][6][7], normal breast tissue [8], breast milk [9], and adrenal and renal carcinomas [10]. Serum PSA levels may be increased in BPH [11,12], prostatitis [12], prostate cancer [13], and following prostate biopsy/massage [14], DRE [15,16], colonoscopy [17], and cystoscopy [18].…”
Section: Discussionmentioning
confidence: 99%
“…Bien que la série de cas soit petite, et que la cause de cette variation demeure peu claire, une différence anatomique marquant deux types d'orgasme a été scientifiquement prouvée [11]. En 2007, Wimpissinger et al décrivent en échographie une structure pouvant correspondre à une prostate féminine mais il semble y avoir eu une confusion avec l'échogénicité du sphincter externe de l'urètre [12].…”
Section: Arguments Pour L'existence Du Point Gunclassified